The Lord is my courage : stepping through the shadows of fear toward the voice of love - Ramsey, K. J. (Grand Rapids, MI. Zondervan Reflective, 2022)
"The Lord Is My Courage is a creative meditation on Psalm 23 that shows courage is more accessible than you think, because courage is something we can practice in order to grow in trust that we have a Good Shepherd who is with us always--no matter where we've been or what we're facing today"--
Keywords: Bible. -- Criticism, interpretation, etc; Courage -- Religious aspects -- Christianity